Sensory reconfigurations during the pandemic: Practices and sound logics of isolation (Revista Argentina de Musicología, 2022)
One of the most disturbing experiences of the pandemic was probably that everyone being globally affected by the same thing. Perhaps by elaborating on the reality of an abrupt and massive affectation we can begin to think about the audible, how it sounds, how a common experience of isolation and distance is heard. Perhaps we should think about the homogenization of formats and experiences. What sensorial matrix does the pandemic open? In this paper we will discuss the concept of sensorium, that is to say, all the ways in which we can perceive with our senses. We want to reflect on how the sensorial experience during the pandemic is translated into a sonorous logic. The article is articulated in three parts, the first of which analyzes some historical-philosophical aspects of changes in sensitivity; secondly, the specifically sonorous declination of the problem; and finally, a drift through the experience of sound artist Cecilia Castro and her survey of what affected her, sonorously, during the pandemic.
Keywords: sound; pandemic; sensorium; listening practices